Nigella plants – traditional uses, bioactive phytoconstituents, preclinical and clinical studies - Salehi, Bahare; Quispe, Cristina; Imran, Muhammad; Ul-Haq, Iahtisham; Živković, Jelena; Abu-Reidah, Ibrahim M.; Sen, Surjit; Taheri, Yasaman; Acharya, Krishnendu; Azadi, Hamed; del Mar Contreras, María; Segura-Carretero, Antonio; et al. (Frontiers Media, 2021)
Nigella is a small genus of the family Ranunculaceae, which includes some popular species due to their culinary and medicinal properties, especially in Eastern Europe, Middle East, Western, and Central Asia. Therefore, this review covers the traditional uses and phytochemical composition of Nigella and, in particular, Nigella sativa. The pharmacological studies reported in vitro, in vivo, and in humans have also been reviewed. One of the main strength of the use of Nigella is that the seeds are rich in the omega-6 fatty acid linoleic acid and provide an extra-source of dietary phytochemicals, including the bioactive thymoquinone, and characteristics saponins, alkaloids, and flavonoids. Among Nigella species, N. sativa L. is the most studied plant from the genus. Due to the phytochemical composition and pharmacological properties, the seed and seed oil from this plant can be considered as good candidates to formulate functional ingredients on the basis of folklore and scientific knowledge. Nonetheless, the main limations are that more studies, especially, clinical trials are required to standardize the results, e.g. to establish active molecules, dosage, chemical profile, long-term effects and impact of cooking/incorporation into foods.